African Samurai The True Story of Yasuke, a Legendary Black Warrior in Feudal Japan - Lockley, Thomas; Girard, Geoffrey (Hanover Square Press, 2019)
Kidnapped as a child, Yasuke had ended up a servant and bodyguard to the head of the Jesuits in Asia, with whom he traversed India and China learning multiple languages as he went. His arrival in Kyoto, however, literally caused a riot. Most Japanese people had never seen an African man before, and many of them saw him as the embodiment of the black-skinned Buddha. Among those who were drawn to his presence was Lord Nobunaga, head of the most powerful clan in Japan, who made Yasuke a samurai in his court. In the four hundred years since, Yasuke has been known in Japan largely as a legendary, perhaps mythical figure. In telling his story, Lockley and Girard offer a new perspective on race in world history and a vivid portrait of life in medieval Japan. -- adapted from jacket